2021
DOI: 10.3390/c7040086
|View full text |Cite
|
Sign up to set email alerts
|

Activated Carbon Impregnated with Elementary Iodine: Applications against Virus- and Bacteria-Related Issues

Abstract: An iodine-doped activated carbon (named IodAC) was developed by adsorbing molecular iodine (I2) on commercially available activated carbon (AC). Iodine was selected with the purpose to add its well-known antibacterial and antiviral properties to the AC and in order to produce an innovative material for environmental pathogens control and for healthcare-related applications. The impregnation method achieved the goal of strongly adsorbing iodine on the AC surface, since both volatility and water solubility resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The disinfecting properties of elemental iodine have long been known. , However, its encapsulation in MOF and release to attack viruses locally is a new concept, as reported by Kirakci and coauthors . Iodine’s mode of action is multifaceted.…”
Section: Eradicationmentioning
confidence: 99%
“…The disinfecting properties of elemental iodine have long been known. , However, its encapsulation in MOF and release to attack viruses locally is a new concept, as reported by Kirakci and coauthors . Iodine’s mode of action is multifaceted.…”
Section: Eradicationmentioning
confidence: 99%
“…These authors achieved a percentage reduction in contamination of 20 to 72%. Natori et al [18], using activated carbon doped with iodine, and Li et al [19], using copper(II) hydroxide nanoparticles associated with carbon, obtained log reduction ranges of 4 and 3 logs, respectively. Compared to these studies, allicin extracts were able to reduce logs by up to 5 logs.…”
Section: Microbiological Analysismentioning
confidence: 99%
“…Then, activated carbon impregnated with biocide properties has already been investigated with successful results, mainly related to the commonly found E. coli strains. Inorganic substances such as iodine-doped activated carbon or cooper hydroxide-coated carbons resulted in high E. coli inhibition efficiency for sanitization, disinfection, sterilization, and even health purposes [18,19]. Adsorbed antibiotics such as sulfamethoxazole and gentamycin also showed huge potential [17].…”
Section: Introductionmentioning
confidence: 99%
“…Its application in face masks, water filtration systems, and air purification stands out as a strategy to contain the spread of infectious diseases. Studies with AC impregnated with iodine have shown excellent results in inhibiting viruses and bacteria, highlighting its potential for disinfection in various applications (Natori et al, 2021). Similarly, the use of silver-loaded AC nanocomposites has demonstrated enhanced antimicrobial activity, presenting itself as a promising antibacterial agent (Devi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%